2017
DOI: 10.1371/journal.pone.0170169
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Single Nucleotide T980C Polymorphism in the Human Carboxypeptidase E Gene Results in Loss of Neuroprotective Function

Abstract: Report of a human with a homozygous truncating null mutation of the Carboxypeptidase E (CPE) gene with endocrinological and neurological deficits prompted us to search for other mutations in the human CPE gene that might be linked to disease. We searched an EST database and identified from a small population of patients, a novel T to C single nucleotide polymorphism (SNP) in the CPE gene at bp980 of exon 4, herein called TC-CPE. This introduces a tryptophan to arginine (W235R) mutation in the catalytic domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, CPE was recently suggested to also function as a growth factor independently of its enzymatic and sorting activities [ 76 ]. Indeed, amongst other reports suggesting a role in neuroprotection [ 77 ], it has recently been shown that CPE regulates cortical neuron migration and dendritic morphology [ 78 ]. However, the degree to which these effects is dependent upon its cargo, which includes other growth factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, CPE was recently suggested to also function as a growth factor independently of its enzymatic and sorting activities [ 76 ]. Indeed, amongst other reports suggesting a role in neuroprotection [ 77 ], it has recently been shown that CPE regulates cortical neuron migration and dendritic morphology [ 78 ]. However, the degree to which these effects is dependent upon its cargo, which includes other growth factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…CPE, which was associated with the aggressive dimension, is a gene highly expressed in brain 54 . Different polymorphisms in this gene have been associated with a loss of neuroprotective function by reducing the effects of the oxidative stress in human cell lines 55 and transgenic mice 56 , leading to memory deficits and depressive behavior 56 . In addition, CPE-knockout mice have shown neurodegeneration in the hippocampus and the prefrontal cortex 57 .…”
Section: Discussionmentioning
confidence: 99%
“…However, CPE was recently suggested to also function as a growth factor independently of its enzymatic and sorting activities [77]. Indeed, amongst other reports suggesting a role in neuroprotection [78], it has recently been shown that CPE regulates cortical neuron migration and dendritic morphology [79]. However, the degree to which these effects is dependent upon its cargo, which includes other growth factors (e.g.…”
Section: Other Novel Differentially Expressed Candidates In Scz Organoidsmentioning
confidence: 99%